Phonological Analysis of the Javanese Language in the Kediri and Bojonegoro Dialects - Adista Larasati; Nagitta Tri Ayunda; Muhammad Farhan Rahmadhani; Herlifah Balqis Nur Aini; Rania Sani Arinnal Haque5; Mario Sebastian Adiputra; Sahda Adilah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This article analyzes the phonological process in the sounding of words in the Kediri and Bojonegoro dialects of Javanese. The analysis of phonology in the Javanese language of Kediri and Bojonegoro dialects is an in-depth analysis of the Javanese language, namely East Java, especially the Kediri dialect with the Bojonegoro dialect. This is interesting to study because the dialects of the two regions are quite unique and have their own characteristics. As well as the lack of research related to the phonological process in regional languages is the background for the author to study the sounding of words in these regional dialects. This research aims to: 1) Knowing the factors that cause sound variations in Kediri and Bojonegoro dialects. 2) Knowing some of the vowel and consonant sound changes that occur in the pronunciation of Kediri and Bojonegoro local languages. In addition to interviews, researchers also analyzed through literature studies. From this study, it was concluded that over time there were several phonological changes in the Kediri and Bojonegoro regional languages. 1) Factors affecting Kediri and Bojonegoro dialect variations include geographical factors, historical background, agreement and language habits by the people of each region. 2) Some changes in vowel and consonant sounds that occur in the pronunciation of Kediri and Bojonegoro include changes in the vowel /i/ to /e/, the vowel /o/ to /ͻ/ and the consonants /l/, /k/ and /ny/. In Kediri and Bojonegoro dialects, there is often an addition of phonemes at the beginning of words, namely the process of prothesis as in the word 'saja' to [ae] in Kediri and [wae] in Bojonegoro. Kediri and Bojonegoro dialects have many variations of phoneme changes in each sound both vowels and consonants. By understanding the factors that cause phonemic changes in the Javanese language of Kediri and Bojonegoro dialects, readers can add to the knowledge related to phonology and this research can be the basis for further research in morphophonemic research.